The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpsyt.2021.623136
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Food in the Family Relationships of Adolescents With Anorexia Nervosa and Bulimia in Northeastern Brazil: A Qualitative Study Using Photo Elicitation

Abstract: Family components can play roles both as protective factors and maintenance mechanisms of eating disorders. We aimed to investigate the role of food in the family relationships of adolescents with anorexia nervosa and bulimia in northeastern Brazil. Using photo elicitation, a visual narrative method that gives insight into the participants' perspective through photograph, we conducted semi-structured interviews with 26 people: four teenage girls with anorexia, four with bulimia, eight mothers, four fathers, fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Several studies reported the potential of arts-based research methods to elicit information that is not readily expressed in words or text. [36][37][38][39][40] Several authors argued that ABM allowed for participants' viewpoints to be represented with greater authenticity and depth. 2,37,[40][41][42][43][44] Young people were also reported to be able to better disclose and share complex and difficult experiences and emotions.…”
Section: Enriching Data Through Arts-based Research Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies reported the potential of arts-based research methods to elicit information that is not readily expressed in words or text. [36][37][38][39][40] Several authors argued that ABM allowed for participants' viewpoints to be represented with greater authenticity and depth. 2,37,[40][41][42][43][44] Young people were also reported to be able to better disclose and share complex and difficult experiences and emotions.…”
Section: Enriching Data Through Arts-based Research Methodsmentioning
confidence: 99%
“…[36][37][38][39][40] Several authors argued that ABM allowed for participants' viewpoints to be represented with greater authenticity and depth. 2,37,[40][41][42][43][44] Young people were also reported to be able to better disclose and share complex and difficult experiences and emotions. 2,36,[44][45][46][47] 3.2.2 | Engaging young people with complex psychosocial needs ABM were found to be highly engaging for young people who are traditionally hard to reach and retain in research.…”
Section: Enriching Data Through Arts-based Research Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parental rejection is defined by Rohner and Rohner (1981) as the lack of warmth and affection from parents towards their children. Considering the role of family that is both a risk and a protective factor in eating disorders (Erriu et al 2020, Ramalho et al 2021) and poor motherhood contributes to disordered eating (Prescott & Le Poire 2002), the role of maternal rejection in the development of ON needed to be evaluated.…”
Section: Introductionmentioning
confidence: 99%